(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
The cleaning efficiency of the machine-picked S-6524 selected grade 2 cotton in the UXK unit of the technology was 80.4% on average, and it showed that it was 12 (abs)% less than the cleaning efficiency of the passport when cleaning high-grade cotton. After the UXK unit, when cotton is cleaned in the 5DP-130 type saw gin supplier-cleaner, the cleaning efficiency of the supplier is equal to 10.1% on average, and it is found that it is 4.9 (abs)% less than the cleaning efficiency in the technical characteristics. The productivity of the gin when ginned in the cleaned cotton gin was on average 1261 kg/h, which was 30% lower than the productivity in the passport. When the ginned fiber was cleaned in the post-ginning fiber cleaner, the mass fraction of defective fiber and impurity in the fiber was high, on average 2.36%. It was determined that the high mass fraction of defective fibers and dirty impurities in the fiber composition is due to the insufficient separation of small impurities from the cotton content in the UXK aggregate. It was studied that adding additional working parts to the unit is not possible from the point of view of technical requirements and causes additional consumption of electricity and spare parts. It was determined that in order to effectively clean cotton from small impurities before the ginning process, to increase gin productivity, and to improve the quality of produced fiber and seed, it is necessary to improve the mesh surface, which is the main working part that performs the process of cleaning cotton from small impurities in the gin supplier-cleaner.